Ancient schwannoma of the infratemporal fossa - Balasubramaniam, Saravanan (Ann Maxillofac Surg, 2014)
Schwannomas are benign tumors of neurogenic origin arising from the Schwann cells of peripheral, cranial, and autonomic nerves. Schwannomas in spite of constituting 25-40% of head and neck tumors the percentage of intraoral schwannomas is merely 1%. Among the intraoral schwannoma the occurrence of the variant “ancient schwannoma of the infratemporal fossa with an intraoral presentation is very rare. The purpose of this presentation is to highlight the rarity of this lesion, to stress the importance of an accurate diagnosis and to consider neurogenic lesions in the differential diagnosis of head and neck lesions.